Synthesis and Biological Evaluation of Some Novel Thiophene-bearing Quinazoline Derivatives as EGFR Inhibitors - Zou, Min; Jin, Bo; Liu, Yanrong; Chen, Huiping; Zhang, Zhuangli; Zhang, Changzheng; Zhao, Zhihong; Zheng, Liyun (Letters in Drug Design & Discovery, 2019)
Background: With the approval of gefitinib, erlotinib, afatinib, and osimertinib for clinical use, targeting Epidermal Growth Factor Receptor (EGFR) has been intensively pursued. Similar to most therapies, challenges related to the treatment resistance against these drugs have emerged over time, so new EGFR Tyrosine Kinase Inhibitors (TKIs) need to be developed. This study aimed to investigate the potential use of a series of thiophene-bearing quinazoline derivatives as EGFR inhibitors. We designed and synthesized nine quinazolin derivatives, among which five compounds (5e, 5f, 5g, 5h, and 5i) were reported for the first time. Methods: Two cancer cell lines, A431 (overexpressing EGFR) and A549 (EGFR wild-type and Kras mutation), were treated by these compounds and subjected to MTT assay. The A431 cells were selected for further treatment (5e) and Western blot analysis. Results: Although the compounds exerted no obvious effects on the proliferation of A549 cells, seven out of the nine compounds significantly inhibited the growth of A431 cells. In particular, the IC50 values of 5e and erlotinib were nearly equal. Western blot results showed that 5e significantly inhibited EGFR autophosphorylation in A431 cells. Structure-activity relationships indicated that quinazolines bearing 6,7-side chains were more potent than those unsubstituted at the 6,7-positions. Moreover, electron-withdrawing hydrophobic groups on the 5-position of the thiophene were preferred, such as chlorine or bromine atom. Conclusion: Nine 4-aminoquinazolin derivatives were designed, synthesized, and evaluated against A431 and A549 cell lines. Seven compounds significantly inhibited the growth of A431 cells. In particular, 5e possessed similar antitumor potency to that of erlotinib.
Keywords: 4-Aminoquinazoline